2023
DOI: 10.1002/adma.202208821
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Durable Alkaline Hydrogen Oxidation Reaction at the Electron‐Deficient Ruthenium–Ruthenium Oxide Interface

Abstract: The slow hydrogen oxidation reaction (HOR) kinetics under alkaline conditions remain a critical challenge for the practical application of alkaline exchange membrane fuel cells. Herein, Ru/RuO2 in‐plane heterostructures are designed with abundant active Ru–RuO2 interface domains as efficient electrocatalysts for the HOR in alkaline media. The experimental and theoretical results demonstrate that interfacial Ru and RuO2 domains at Ru–RuO2 interfaces are the optimal H and OH adsorption sites, respectively, endow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…The strong electron-withdrawing effect of MoO 3 could easily cause Ru to become electron deficient, which is beneficial for the improvement of hydrogen absorption strength, and thus hindering the hydrogen desorption. [32] The Mo 3d XPS spectra of MoO 2 NT, MoO 2 @Ru NT, and MoO 2 /MoO 3 @Ru NT reveal the existence of Mo 4+ , Mo 5+ , and Mo 6+ , in which the existence of high valent Mo (i.e., Mo 5+ and Mo 6+ ) could be attributed to the surface MoO 2 being easily susceptible to oxidation in the air (Figures S7a-S9a, Supporting Information). [33,34] The Mo 3d spectrum of MoO 3 @Ru NT presents the deconvolutions of Mo 5+ and Mo 6+ (Figure S10a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The strong electron-withdrawing effect of MoO 3 could easily cause Ru to become electron deficient, which is beneficial for the improvement of hydrogen absorption strength, and thus hindering the hydrogen desorption. [32] The Mo 3d XPS spectra of MoO 2 NT, MoO 2 @Ru NT, and MoO 2 /MoO 3 @Ru NT reveal the existence of Mo 4+ , Mo 5+ , and Mo 6+ , in which the existence of high valent Mo (i.e., Mo 5+ and Mo 6+ ) could be attributed to the surface MoO 2 being easily susceptible to oxidation in the air (Figures S7a-S9a, Supporting Information). [33,34] The Mo 3d spectrum of MoO 3 @Ru NT presents the deconvolutions of Mo 5+ and Mo 6+ (Figure S10a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The MOC-Ru shows higher current density in the whole potential range than the C-Ru, which can be attributed to the low oxophilicity of MOC-Ru and alleviated poisoning of Ru sites by OH * . [19,42] Besides, the MOC-Ru shows a lower average ΔG OH* (−0.39 eV) than that of C-Ru (−0.64 eV), which suggests the weakened Ru-OH * affinity and favorable OH * desorption (Figure 5d). This reflects the significant role of MOC in the construction of low oxophilic microenvironments in MOC-Ru, which efficiently alleviates the occupation of Ru sites by OH * .…”
Section: Resultsmentioning
confidence: 99%
“…The E peak of Ru/VOC is lower than that of Ru/C, indicating the weaker HBE of Ru/VOC. It is reported that the HBE on metal can be modulated by alloying and heterojunctions. However, no Ru–V bond signal and Ru structure changes were observed in a series of characterizations for Ru/VOC, and the regulation of HBE in Ru/VOC was achieved by facilitating electron transfer between the Ru nanoparticles and carbon support through doping the carbon matrix with the atomically dispersed V–O species. In addition, the OHBE of V sites and Ru sites was also assessed by CO stripping experiments on VOC and Ru/C, respectively.…”
Section: Resultsmentioning
confidence: 99%